1999
DOI: 10.1046/j.1432-1327.1999.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of indole‐3‐acetic acid in Azospirillum brasilense

Abstract: Quantum chemical methods AM1 and PM3 and chromatographic methods were used to qualitatively characterize pathways of bacterial production of indole-3-acetic acid (IAA). The standard free energy changes (DG8 H sum ) for the synthesis of tryptophan (Trp) from chorismic acid via anthranilic acid and indole were calculated, as were those for several possible pathways for the synthesis of IAA from Trp, namely via indole-3-acetamide (IAM), indole-3-pyruvic acid (IPyA), and indole-3-acetonitrile (IAN). The DG8 H sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 29 publications
3
32
0
9
Order By: Relevance
“…22 Zakharova et al 23 showed that several bacterial IAA biosynthetic pathways might exist in Azospirillum brasilense, a nitrogen-fixing bacterium found in the rhizosphere of various grass species. IAA can be synthesized from Trp through IAM, IPA, and IAN pathways in A. brasilense.…”
Section: Iaa Biosynthetic Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Zakharova et al 23 showed that several bacterial IAA biosynthetic pathways might exist in Azospirillum brasilense, a nitrogen-fixing bacterium found in the rhizosphere of various grass species. IAA can be synthesized from Trp through IAM, IPA, and IAN pathways in A. brasilense.…”
Section: Iaa Biosynthetic Pathwaysmentioning
confidence: 99%
“…IAA can be synthesized from Trp through IAM, IPA, and IAN pathways in A. brasilense. 23 However, feeding experiments with labeled precursors have indicated that Trp-independent IAA production in A. brasilense is derived from the intermediates of Trp pathways. 4,23 However, no specific enzymes or genes of this pathway have yet been identified, and only a few studies on the IAA biosynthetic pathway in fungi have been conducted.…”
Section: Iaa Biosynthetic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, alguns autores sugerem que 80% do ácido indolacético sintetizado por este gênero é derivado de uma via independente da adição de triptofano ao meio de cultura, pois outros compostos podem ser metabolizados (ZAKHAROVA et al, 1999). De acordo com Ona et al (2005), a produção de AIA só ocorre sob condições do que o gene 16S rDNA e os genes rrs (Ribossomais).…”
Section: Isolamento Das Bactérias Diazotróficasunclassified
“…In either case, their effects on plant growth are pronounced. ePGPR increase plant growth directly through the production of phytohormones (Zakharova et al 1999), or the facilitation nutrient uptake (Glick 1995). Indirect promotion of plant growth is through antibiosis via antibiotic type compounds (Maurhofer et al 1992), through siderophores that bind available Fe (Carson et al 2000) or enhanced resistance to biotic stresses and/or abiotic stresses such as frost damage (Sturz et al 2000).…”
Section: Conventional Roles In Plant Growth Promotionmentioning
confidence: 99%